The Influence of Electronic Word of Mouth (E-WOM) on Self-Control-Moderated Purchasing Decisions - Marsyanda Ivalda; Baiq Handayani Rinuastuti (LP2M IAIN Palopo, 2026)
The rapid growth of e-commerce in Indonesia, driven by digital technology and social media, has elevated Electronic Word of Mouth (E-WOM) as a key influencer of consumer purchase decisions, although moderated by psychological factors such as self-control. This study aims to analyze E-WOM's effect on purchase decisions moderated by self-control among Indonesian e-commerce users. Employing a quantitative causal-explanatory design, data were collected via Likert-scale questionnaires from 100 purposive respondents and analyzed using SEM-PLS in SmartPLS 4. Results reveal E-WOM positively and significantly influences purchase decisions (β=0.373, t=4.207, p=0.000), while self-control negatively moderates this relationship (β=-0.075, t=1.961, p=0.050), weakening E-WOM's impact at higher self-control levels. The model explains 62% variance (R²=0.620). In conclusion, while E-WOM drives purchases, self-control enables rational decision-making, offering implications for ethical e-commerce marketing.